QOL-12. CLINICAL SIGNIFICANCE OF RADIATION-INDUCED CEREBROVASULAR DISEASE IN CHILDHOOD BRAIN TUMOR SURVIVORS. (4th December 2020) - Remes, Tiina; Suo-Palosaari, Maria; Ritari, Niina; Puosi, Riina; Koskenkorva, Päivi; Sutela, Anna; Toiviainen-Salo, Sanna-Maria; Arikoski, Pekka; Arola, Mikko; Hovén, Emma; Lähteenmäki, Päivi; Lönnqvist, Tuula; et al.
Abstract: BACKGROUND: Childhood brain tumor survivors have a high risk of early cerebrovascular disease, but currently its clinical significance is unknown. METHODS: In a nation-wide study, we investigated 68 childhood brain tumor survivors treated with radiotherapy by using magnetic resonance imaging (MRI) and neuropsychological examination after median follow-up time of 20.6 years (range 5.0 – 33.1 years) since radiotherapy. Associations between imaging markers of cerebrovascular disease, white matter hyperintensities and the results of neuropsychological examination were investigated. RESULTS: Majority (65 %) of the survivors was diagnosed with cerebrovascular disease at median age of 27.1 years (range16.2 – 43.8 years). The presence of imaging markers of cerebrovascular disease or white matter hyperintensities was associated with poorer performance in verbal (VIQ) and performance (PIQ) intelligent quotient, working and semantic memory, executive functions, visuospatial ability, and immediate and general auditive memory ( P < 0.05). Survivors with microbleeds performed worse in PIQ, processing speed, executive functions, and visuospatial ability ( P <0.05). Lacunar infarcts were associated with difficulties in visuospatial ability ( P <0.05). Survivors with white matter hyperintensities in MRI had higher impairment of working and semantic memory, visuospatial ability, and general auditive memory ( P < 0.05). Cerebrovascular and small-vessel disease burden associated with poorer neurocognitive performance. CONCLUSION: The imaging markers of cerebrovascular disease and white matter hyperintensities were related to poorer cognitive performance in radiation-treated long-term survivors of childhood brain tumor. Longitudinal studies are urgently needed to investigate how cerebrovascular disease and related cognitive impairment progress in the survivors.